2012
DOI: 10.1371/journal.pone.0051518
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef Breaches Placental Barrier in Rat Model

Abstract: The vertical transmission of HIV-1 from the mother to fetus is known, but the molecular mechanism regulating this transmission is not fully characterized. The fetus is highly protected by the placenta, which does not permit microbial pathogens to cross the placental barrier. In the present study, a rat model was established to observe the effect of HIV-1 protein Nef on placental barrier. Evans blue dye was used to assay permeability of placental barrier and fourteen day pregnant Sprague Dawley rats were inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Components of HIV such as Nef have complex effects on the immune system, including CD4 depletion, activation, and apoptosis ( 32 , 33 ). Furthermore, in a rodent model, Nef breaches placental barrier function and may enable HIV, other viral proteins and microbial products (see below) to cross the placenta ( 34 ), potentially exacerbating effects on the fetal immune system.…”
Section: Morbidity and Mortality Of Heu Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Components of HIV such as Nef have complex effects on the immune system, including CD4 depletion, activation, and apoptosis ( 32 , 33 ). Furthermore, in a rodent model, Nef breaches placental barrier function and may enable HIV, other viral proteins and microbial products (see below) to cross the placenta ( 34 ), potentially exacerbating effects on the fetal immune system.…”
Section: Morbidity and Mortality Of Heu Infantsmentioning
confidence: 99%
“…In an animal model ( 62 ), subclinical infection with murine gammaherpesvirus 68 sensitizes pregnant mice to a greater cytokine response to LPS, suggesting that viral infections have potential to amplify the impact of LPS exposure during pregnancy. Maternal microbial translocation in HIV-affected pregnancies may plausibly contribute to immune activation in HEU infants: LPS can cross the placental barrier in mice ( 63 ), meaning that translocated maternal LPS could potentially activate fetal immune cells, particularly in the context of Nef-mediated placental barrier dysfunction ( 34 ). Whether LPS or other microbial products cross the placental barrier in HEU infants and contribute to immune activation has yet to be confirmed.…”
Section: Morbidity and Mortality Of Heu Infantsmentioning
confidence: 99%
“…The paper by SimĂ”es et al reports a significant increase in IL-1 ÎČ , IL-6, and TNF αÎČ levels in the offspring brain in response to maternal cytokines [ 166 ]. The inflammatory response leads to an increase in ROS generation by endothelial cells, and, consequently, to disruption of BBB permeability [ 167 ]. In addition to the disruption of BBB and placental barrier permeability, cytokines in the brain regulate the expression of major histocompatibility complex I (MHC I), coordinating synaptic pruning [ 168 , 169 ].…”
Section: Molecular Mechanisms Of Oxidative Stress In the Pathogenementioning
confidence: 99%
“…For successful infection, viruses have developed several strategies to promote an ideal microenvironment in order to maintain viral persistence and optimize their infection cycle (Amara and Mercer 2015;Harak and Lohmann 2015;Vijaykrishna, Mukerji and Smith 2015). Several studies have reported the mechanisms via which viruses infecting the maternal-fetal interface can promote a series of pathogenic processes; these processes greatly depend on the expression of specific viral genes whose products are key players in the replication and efficient dissemination of the viruses (Singh et al 2012;Aldo et al 2016). For the purpose of this minireview, these pathogenic mechanisms will be classified with respect to the following: (i) modulation of cell apoptosis; (ii) impact of the immune response; and (iii) mechanisms underlying invasion and vascular damage during viral infection.…”
Section: Pathogenic Mechanisms In Trophoblasts During Viral Infectionsmentioning
confidence: 99%